Australian female athlete perceptions of the challenges associated with training and competing when menstrual symptoms are present. Issue 3 (June 2020) - Armour, Mike; Parry, Kelly A; Steel, Kylie; Smith, Caroline A
Coaches consider various competencies (e.g. conditioning, nutrition, skills and tactics), when planning sessions, though rarely the impact of menstruation on the efficacy of training and competition performance for athletes. Given the impact menstrual symptoms can have on athletes, the management strategies that athletes may use to minimise any potential impact, and the mechanisms that provide barriers to greater coach athlete interaction require investigation and consideration. Therefore, this study aimed to investigate the strategies used by athletes to manage menstrual symptoms and the role coaches played in this process. An anonymous, 36-item questionnaire was developed and hosted on Qualtrics. Descriptive statistics and Chi-square statistics were used to analyse the data. One hundred and twenty-four valid responses from Australian athletes 16–45, with a mean age of 29 years, were received. Period pain (82%) and pre-menstrual symptoms (83%) were commonly reported and contributed to fatigue and to perceived reductions in performance during or just prior to the period (50.0% in training, 58.7% on 'game day'). Contraceptive use was reported by 42% of athletes. Those reporting heavy menstrual bleeding (29.7%) were more likely to report increased fatigue (relative risk 1.6, 95% CI 1.07 to 2.32). Over three-quarters of athletes reported neither they nor their coaches altered training due to the menstrual cycle. Most athletes (76%) did not discuss menstruation with their coaches. Given the perceived negative impact on performance and potential risks with contraceptive usage during adolescence, coaches, trainers and athletes need to have a more open dialogue around the menstrual cycle.